Correlation Between The Comprehension of Arabic Vocabulary and Speaking Skill Among Students at The Islamic High School at Riau Institute of Technology in Pekanbaru - Nopel, Perisi; Suja, Aidillah (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeru Sultan Aji Muhammad Idris Samarinda, 2022)
This research is correlational research. There are two variables in this research, namely variable X (comprehension of vocabulary) and variable Y (speech skill). As for the research individual, it is among students at the Islamic High School at Riau Institute of Technology in Pekanbaru and its position is between the comprehension of Arabic vocabulary and the skill of speaking. This research introduces test tools in the comprehension of Arabic vocabulary, the researcher uses Written test on the face of multiple testing, the researcher continuously presents the incomplete speech with four choices to complete the speech. Then, for speaking skill, the researcher presents an oral test that deals with conversation with the students on a chosen topic. The community in this research is 24 students. Then, in sampling, the researcher introduces the sample group method. Using the product moment in SPSS 17.00, the researcher finds r null 0.576 and r tabel 0.423 in the 5% range and 0.537 in the 1% range. Therefor r null is greater than r tabel in the 5% and 1% cycle (Ho is negligible and Ha is acceptable). On this concept, there is an important correlation between the comprehension of Arabic vocabulary on speaking skill. Then the researcher finds that the comprehension of Arabic vocabulary affects speaking skill by 34.18%. In conclusion, 34.18% affected the comprehension of Arabic vocabulary on the speaking skill of students at the Islamic High School at the Riau Institute of Technology in Pekanbaru, then 65.82% affected by other factors.